The Effect of Environment, Training, Motivation, and Satisfaction on Work Productivity - Hairo, Astrid Meutia; Martono, S. (Management Analysis Journal, 2019)
The purpose of this study is to examine the effect of the work environment, job training, work motivation, and job satisfaction on work productivity. The number of samples in this study were 86 employees with saturated sampling techniques. Data collection method using a uestionnaire. Data analysis using percentage descriptive analysis, classical assumption, multiple regression analysis, and determination coefficient. The result show that there is a significant influence between work environment, job training, work motivation, and job satisfaction on work productivity. The better the work environment and the quality of training, the higher the motivation and job satisfaction will further increase employee work productivity. To maintain the work environment, job training, work motivation, and job satisfaction given to employees, the objectives can be achieved.